Model Development for Service Quality in Hotel Management through Confirmatory Factor Analysis (International Journal of Food and Nutritional Sciences, 2023)
In the hospitality sector, service quality is a major factor influencing client satisfaction, loyalty, and overall performance. To keep being competitive and satisfy guests' changing expectations, hotels must consistently analyze and improve service quality. The study aimed to create a postulated model of service quality in management. The measure is made up of 25 statements categorized into five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. 189 people were recruited for the study using the judgment sampling technique. The researcher provided the interview schedule in printed form after translating it into the local language to guarantee high content validity. The underlying dimensions were found by reducing the data using factor analysis. Each dimension's factors were kept at a cut-off score of 0.5. Confirmatory Factor Analysis (CFA) was used to test all of the retrieved factors that were taken into account when building the suggested model. The pattern matrix results produced by factor analysis using SPSS served as the source of the input data for CFA. The dimensional structure of service quality in hotel management was validated by the CFA results. The study offers a trustworthy measuring model that can be applied to evaluate and improve hotel service quality.